Intelligent Character Islamic Education Teachers in Fostering Digital Civility - Ibnu Sahal Alburhani; Asep Dahliyana; Imas Kurniawaty (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
The rapid development of digital technology has transformed the educational landscape, presenting both opportunities and challenges for Islamic religious education. One of the main challenges is fostering digital civility polite, ethical, and responsible behavior in cyberspace that aligns with the principles of adab in Islam. This study aims to analyze the role of intelligent character Islamic religious education teachers in shaping students’ digital civility, as well as to formulate relevant guidance strategies in the digital era. The method employed is library research with a qualitative approach, utilizing classical and contemporary literature from primary and secondary sources selected based on strict inclusion and exclusion criteria. Analysis was conducted through descriptive analytical methods, content analysis, and philosophical hermeneutics. The findings indicate that Islamic religious education teachers who integrate intellectual, emotional, social, and spiritual intelligence can serve as role models and mentors in instilling adab values in the digital space. Effective strategies include integrating Islamic values with digital literacy in the curriculum, implementing creative project based learning, and providing continuous guidance in addressing students’ online ethical dilemmas. The identified challenges include the digital literacy gap between teachers and students, institutional barriers, and the overwhelming flow of negative content. This study affirms that fostering digital civility requires a combination of technical competence, moral spiritual guidance, and ongoing collaboration among schools, families, and communities.